2020
DOI: 10.1186/s13059-020-1940-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematic functional identification of cancer multi-drug resistance genes

Abstract: Background Drug resistance is a major obstacle in cancer therapy. To elucidate the genetic factors that regulate sensitivity to anti-cancer drugs, we performed CRISPR-Cas9 knockout screens for resistance to a spectrum of drugs. Results In addition to known drug targets and resistance mechanisms, this study revealed novel insights into drug mechanisms of action, including cellular transporters, drug target effectors, and genes involved in target-relevant pathways. Importantly, we identified ten multi-drug resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 43 publications
(48 reference statements)
0
22
0
Order By: Relevance
“…Building on this work, the Neely group used HAP1 cells in combination with a CRISPR screening approach (GeCKO.v2 library) to identify resistance-causing loss-of-function mutations against paclitaxel, but extended their efforts to include an additional panel of 26 anticancer drugs. Among others, they identified the previously uncharacterized open reading frame C1orf115, containing a DUF4710 domain of unknown function, to convey robust resistance to paclitaxel, vincristine and the purine analog cladribine [ 161 ], suggesting C1orf115 to be an uncharacterized multidrug resistance gene that escaped previous identification. In contrast, Wei et al used cervical squamous cell carcinoma cells and the GeCKO.v2 library to identify paclitaxel-sensitizing genes.…”
Section: Mode Of Action Resistance Mechanisms and Vulnerabilitiesmentioning
confidence: 99%
“…Building on this work, the Neely group used HAP1 cells in combination with a CRISPR screening approach (GeCKO.v2 library) to identify resistance-causing loss-of-function mutations against paclitaxel, but extended their efforts to include an additional panel of 26 anticancer drugs. Among others, they identified the previously uncharacterized open reading frame C1orf115, containing a DUF4710 domain of unknown function, to convey robust resistance to paclitaxel, vincristine and the purine analog cladribine [ 161 ], suggesting C1orf115 to be an uncharacterized multidrug resistance gene that escaped previous identification. In contrast, Wei et al used cervical squamous cell carcinoma cells and the GeCKO.v2 library to identify paclitaxel-sensitizing genes.…”
Section: Mode Of Action Resistance Mechanisms and Vulnerabilitiesmentioning
confidence: 99%
“…2016 ), berry color in grapes ( Zhou et al. 2019 ), awn length in basmati rice ( Choi et al. 2020 ), and the loss of the jointed fruit pedicel ( Soyk et al.…”
Section: Introductionmentioning
confidence: 99%
“…Two miRNAs (hsa-miR-877-5p and hsa-miR-4496) were also included in final ceRNA hub regulatory network. It has been reported that the loss of C1orf115 can lead to the resistance to five anticancer drugs, and the low expression of C1orf115 is related to the poor prognosis of many cancers ( Lau et al, 2020 ). Besides, Senchenko et al (2013) proved that PRICKLE2 was significantly related to the prognosis of various cancers.…”
Section: Discussionmentioning
confidence: 99%